How to become CEO : - Fox, Jeffrey J. (Hyperion, 1998)
Vision, persistence, integrity, and respect for everyone in the workplace--these are all qualities of successful leaders. But Jeffrey J. Fox, the founder of a marketing consulting company, also gives these tips: never write a nasty memo, skip all office parties, and overpay your people. These are a few of his key ways to climb the corporate ladder.